CRYPTOCURRENCY TREND IN INDONESIA: A REGULATORY APPROACH TO SOLVE NUMEROUS ECONOMIC PROBLEMS - Gunardi Gunardi; Lewiandy Lewiandy (PROSIDING SERINA, 2021)
Cryptocurrensy is a new technology and poses a new challenge to the regulators in making regulatory framework of the digital currency. In this paper, we analyze the potential economics problems that might persists with the increase trend of cryptocurrency and we, then, later analyze the suitable regulation to deal with the problems. The problems identified in this paper are the transaction cost problem of ‘double spending’. The rise of shadow economy, externality problem related to the environmental pollution and the herding behavior of the investors. We use De Geest’s ‘N Problems Requires N Solutions’ approach to provide the regulatory prescription, where each economic problem needs different solution. The arguments established to deal with each problems varies depending on the problem. The transaction cost problem of ‘double-spending’ will be self-regulatory through competition, therefore requires no regulatory approach. The problem of shadow economy will require administrative regulation. The present positive environmental law in Indonesia, or its extention of scope, would suffice to deal with the externality problem of environmental pollution. Lastly, the problem of herding behaviour of the investors would require information disclosure regulation. Cryptocurrency merupakan sebuah teknologi baru dan merupakan sebuah tantangan baru bagi para regulator dalam membuat aturan terkait perkembangan cryptocurrency. Dalam tulisan ini kami menganalisis potensi permasalahan ekonomi yang muncul dengan meningkatnya tren cryptocurrency dan menganalisis aplikasi regulasi yang tepat untuk menyelesaikan permasalahan tersebut. Permasalahan yang kami identifikasi antara lain masalah biaya transaksi dengan adanya ‘biaya ganda’, kebangkitan ekonomi ilegal, permasalahan eksternalitas terkait polusi lingkungan dan masalah perilaku kawanan. Pendekatan yang kami lakukan dalam melihat permasalahan multidimensi ini adalah dengan pendekatan “n permasalahan membutuhkan n solusi” dari De Geest, di mana setiap masalah memerlukan solusi yang berbeda. Argumentasi yang dibangun untuk solusi tiap permasalahan di atas bervariasi. Permasalahan biaya transaksi akan diselesaikan dengan kompetisi dan tidak memerlukan regulasi. Permasalahan ekonomi ilegal dapat diatasi dengan regulasi administratif. Permasalahan eksternalitas terkait lingkungan hidup dapat diatasi dengan hukum lingkungan positif saat ini atau perluasannya, jika diperlukan. Terakhir, permasalahan perilaku kawanan para investor dapat diatasi dengan regulasi keterbukaan informasi.